Effects of Growth Hormone and Insulin-Like Growth Factor-1 on Postoperative Muscle and Substrate Metabolism. (9th November 2009) - Hammarqvist, Folke; Wennström, Ingmar; Wernerman, Jan
Abstract : This study explored if a combined supplementation of GH and IGF-1 had an additive effect on whole body nitrogen economy, energy, substrate and skeletal muscle metabolism following surgical trauma. Patients were randomized to controls (C;n = 10 ), to GH (0.15 IU/kg/injection) (GH;n = 7 ) or GH combined with IGF-1 (40 μ g/kg/injection) subcutaneously twice a day (GH-IGF-1;n = 9 ) together with standardized parenteral nutrition. Muscle amino acids, glutathione and the ribosomal pattern reflecting protein synthesis, and nitrogen balance were measured. GH- and GH-IGF-1 groups showed lower urea and higher plasma glucose concentrations. Energy expenditure increased in the GH-group. GH-IGF-1 prevented a decrease in muscle polyribosomes indicating a preserved muscle protein synthesis. In the GH group unaltered BCAA and AAA levels were seen in muscle indicating an unchanged protein breakdown, while the other groups showed increased muscle concentrations postoperatively. Without statistically difference GH marginally improved the nitrogen balance, in terms of higher values, and growth factors improved the nitrogen balance when the shift in urea was taken into account. To conclude, growth factors influences urea metabolism, protein degradation and protein synthesis. There was no clearcut additional effect when combining GH and IGF-1 but the study was probably underpowered to outrule this and effects on nitrogen balance.